The cultural capital gap: an ethnographic study of home and school discourses in a southern Latino community. Issue 1 (2nd January 2020) - Sabrin, Mohammed
ABSTRACT: This study explored the interaction of school and students' cultures at a Latino academic/social enrichment after-school programme in Georgia, USA. I researched if and how students used language, a defining aspect of cultures, as cultural capital while negotiating school and student discourses. This study is particularly important due to the current debates over the definition of American identity. This interpretive ethnographic research utilised Socio-linguistic and Critical Theory lenses. I found that there was a wide disparity in cultural capital between home and school discourses, and that although Latino students in this study realised this and were often disempowered when they did not participate in the mainstream school culture, they also knew how to negotiate between institution and discourse identities at times through their language use to suit their interests. Thus, this article is added evidence in the growing literature that cultural capital can be fluid rather than static.